2021
DOI: 10.1055/s-0041-1728238
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lipoteichoic Acid from Lactobacillus plantarum on Dental Pulp Inflammation

Abstract: Objective Lactobacillus plantarum, a bacterium located in deep caries, has a virulence factor in the form of lipoteichoic acid (LTA), which is found in the bacterial cell wall. LTA is able to trigger a neutrophils response in the dental pulp inflammation process within the first 6 to 24 hours. The quantity of bacteria is one factor influencing the increase in number of neutrophils in addition to the quality of the bacteria. This study seeks to analyze the effect of lipoteichoic acid of Lactobacillus plantarum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies have confirmed that in cases of shallow caries, Gram‐positive bacteria account for a higher proportion, while in cases of deep caries and pulpitis, the proportion of Gram‐negative bacteria is higher [ 6 ]. Previous studies reported that both LTA and LPS were used as an inflammation model for dental pulp cells [ 7 , 8 , 9 , 10 ]. Our previous studies compared dental pulp cell inflammation models constructed using LTA and LPS, and the different treatment times with LTA and LPS (1, 2, 3, 5 and 7 days) [ 5 ].…”
mentioning
confidence: 99%
“…Studies have confirmed that in cases of shallow caries, Gram‐positive bacteria account for a higher proportion, while in cases of deep caries and pulpitis, the proportion of Gram‐negative bacteria is higher [ 6 ]. Previous studies reported that both LTA and LPS were used as an inflammation model for dental pulp cells [ 7 , 8 , 9 , 10 ]. Our previous studies compared dental pulp cell inflammation models constructed using LTA and LPS, and the different treatment times with LTA and LPS (1, 2, 3, 5 and 7 days) [ 5 ].…”
mentioning
confidence: 99%